2022
DOI: 10.1021/acsanm.2c04528
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Carbon Quantum Dots Encapsulated in ZIF-8 Nanoparticles for Turn-On Recognition of Chiral Folic Acid and Nitrofurazone and Applications as Fluorescent Inks

Abstract: Metal−organic frameworks (MOFs) are a kind of nanoporous coordination materials, which have the advantages of high crystallinity and tunable functionalization. Carbon dots (CDs) are zerodimensional luminescent carbon nanomaterials, which combine the advantages of small organic molecules such as fluorophores and conventional semiconductors such as inorganic quantum dots. Chiral quantum dots are appealing for detection of chiral substances due to their unique chirality. In this work, chiral CDs can be loaded int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Ding and colleagues ( Table 1 , entry 11 [ 43 ]) encapsulated CDs into metal-organic frameworks (MOFs) in order to have enantiorecognition of D- and L-folic acid (FA) with a fluorescence sensor. CDs were obtained by a hydrothermal bottom-up method from citric acid and L-Cys as the chiral agent and were encapsulated into a zeolitic imidazolate framework, forming a chiral composite used as a selective and sensitive “turn-on” fluorescent sensor, with a low detection limit (0.31 μM) for L-FA.…”
Section: Fluorescence and Colorimetric Chiral Sensorsmentioning
confidence: 99%
“…Ding and colleagues ( Table 1 , entry 11 [ 43 ]) encapsulated CDs into metal-organic frameworks (MOFs) in order to have enantiorecognition of D- and L-folic acid (FA) with a fluorescence sensor. CDs were obtained by a hydrothermal bottom-up method from citric acid and L-Cys as the chiral agent and were encapsulated into a zeolitic imidazolate framework, forming a chiral composite used as a selective and sensitive “turn-on” fluorescent sensor, with a low detection limit (0.31 μM) for L-FA.…”
Section: Fluorescence and Colorimetric Chiral Sensorsmentioning
confidence: 99%
“…Chiral CDs were encapsulated into zeolitic imidazolate framework-8 (ZIF-8) using an in situ encapsulation method, resulting in the formation of a chiral composite hybrid material called chiral CDs/ZIF-8. 116 Fluorescence experiments showed that chiral CDs/ZIF-8 can function as a highly sensitive and selective “turn-on” fluorescent probe for the detection of d -folic acid and l -folic acid. For d -folic acid, the detection limit was 0.31 μM, while for l -folic acid, the detection limit was 4.36 μM.…”
Section: Individual Chiral Nanomaterials For Sensingmentioning
confidence: 99%
“…20 The unique chiral surface patterns of the CMOF make it a potential candidate for chiral discrimination. For instance, Liu et al 21 reported a CMOF with chiral carbon quantum dots (CCQDs) as the chiral source, which could be used for the fluorescent discrimination of chiral folic acid and nitrofurazone.…”
Section: Introductionmentioning
confidence: 99%